2005
DOI: 10.1080/00288330.2005.9517341
|View full text |Cite
|
Sign up to set email alerts
|

Can additional abundance indices improve harvest control rules for New Zealand rock lobster (Jasus edwardsii) fisheries?

Abstract: Although New Zealand rock lobster (Jasus edwardsii) fisheries can be assessed with a sophisticated Bayesian length-based model, these assessments are expensive and time consuming; they cannot be conducted for each area every year. Harvest control rules are increasingly important management tools in New Zealand rock lobster fisheries. Recent work has developed and evaluated procedures for rebuilding or maintaining lobster stocks based on criteria agreed by stakeholders. Most management procedures depend on a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Our analyses shed no light on which of these two has most weight, but the spatial and temporal consistencies in settlement patterns (Booth et al, 2007), together with the strong correlations reported here, persuade us that by no means does the full burden for lack of consistency between the settlement record and the modelled recruitment lie with the settlement record. Further, the lack of consistency between the settlement indices and fishery performance described by Bentley et al (2005b) may lie in the improbably small lags they used between settlement and recruitment to the fishery (e.g., just 3 years for CRA 7) and, apparently, the amalgamating of male and female CPUE data in fisheries where the sexes recruit at very different ages.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Our analyses shed no light on which of these two has most weight, but the spatial and temporal consistencies in settlement patterns (Booth et al, 2007), together with the strong correlations reported here, persuade us that by no means does the full burden for lack of consistency between the settlement record and the modelled recruitment lie with the settlement record. Further, the lack of consistency between the settlement indices and fishery performance described by Bentley et al (2005b) may lie in the improbably small lags they used between settlement and recruitment to the fishery (e.g., just 3 years for CRA 7) and, apparently, the amalgamating of male and female CPUE data in fisheries where the sexes recruit at very different ages.…”
Section: Discussionmentioning
confidence: 93%
“…We found no concurrence between field estimates of recruitment and modelled estimates of fishery recruitment when a 2-year lag between settlement and recruitment to the model was applied, suggesting that year-to-year rates of recruitment to the fishery have been interpreted differently in the two approaches. Bentley et al (2004aBentley et al ( , 2005b concluded that settlement indices were not useful in predicting fishery performance because of the lack of consistency with modelled recruitment. As emphasised by Bentley et al (2004a), this may be because (1) the estimates of recruitment from stock assessments may be imprecise -at least in part because the stock assessment model is designed primarily to model that part of the population that is vulnerable to the fishery, not recruitment; and/or (2) the collector indices may not be providing good information on recruitment.…”
Section: Discussionmentioning
confidence: 98%
“…In particular, long-term declines were likely where initial choices for exploitation rates were based on biased biomass estimates. Data-based procedures have been developed and adopted for Namibian hake and South African west coast rock lobster (Rademeyer et al, 2007) and New Zealand rock lobster (Bentley et al, 2005), although procedures for hake and rock lobster in South Africa were both considered interim in the absence of better quality data for future model-based procedures.…”
Section: Discussionmentioning
confidence: 99%
“…A management strategy, also referred to as a "management procedure" (Bentley and Langley 2012), a "harvest control rule" (Kell et al 1999, Breen 2009, and a "decision rule" (Bentley et al 2005), is a group of regulations defined with key management parameters to address certain management objectives (Deroba and Bence 2008). Fishing mortality of the next year can be determined directly or indirectly using a defined management strategy based on the status of the stock and/or exploitation determined in a stock assessment.…”
Section: Introductionmentioning
confidence: 99%